Distribution of indigenous freshwater fishes in the central coastal region of Shertallai, Kerala - Jayasree, M; Sabesan, S; Krishnamoorthy, K; Panicker, K N (Indian Journal of Fisheries, 2011)
Use of indigenous fish species in the controlof vector breeding is being encourageddue to their natural adaptation in a given area.Preliminary survey on the prevalence of fishspecies is a prerequisite lor the identificationof potential larvivorous fishes and their associationwith other co-existing species. Sucha survey was carried out in Shertallai taluk inKerala State, to develop vector controlstrategies with larvivorous fishes in an integratedapproach to contain Malayanfilariasis, known to he endemic for manydecades in the region (Rajagopalan et al.1988).